A longitudinal study examining the influence of diet-related compensatory behavior on healthy weight management. (1st January 2021) - Sob, Cynthia; Siegrist, Michael; Hagmann, Désirée; Hartmann, Christina
Abstract: The aim of the present study was to examine the role of diet-related compensatory behavior in healthy weight management regarding diet quality, physical activity, and body mass index (BMI) over time in a non-clinical general population. Data were based on the first and third waves of the Swiss Food Panel 2.0 survey, which included questions about food consumption frequencies and constructs measuring weight management strategies. Data were examined using principal component analysis and correlation analyses to examine the psychometric properties of the adapted items, and multiple linear regression analyses for longitudinal examination. The adapted items measuring diet-related compensatory behavior were shown to be valid and reliable. On a longitudinal level, the results show that diet-related compensatory behavior was a significant predictor for change in physical activity and diet quality. With a higher tendency for diet-related compensatory behavior, physical activity and diet quality increased after two years. No effect was found for changes in BMI over time. Individuals from a non-clinical population showing diet-related compensatory behavior more frequently seem to have an improved diet quality and an increase in physical activity over time. Therefore, when applied in healthy doses, diet-related compensatory behavior may contribute to the maintenance of a balanced and healthy body weight, but it is not a successful strategy for weight loss over time.